Physical Properties of Gel and Edible Plastic from Whey and Tapioca In Various Ratio and pH Value - Triana Lindriati; Herlina .; Ahmad Nafi (UNEJ e-Proceeding, 2014)
Edible plastic usually made from hydrocolloids and could be produced by solvent casting method whereas gel was made before casting. Potential of whey protein combined with tapioca as edible plastic based component was studied at this research. pH of solvent could affect interaction of whey and tapioca during  gel preparation. The gel’s characters affected on plastic’s characters . The research objectives were to study effect of whey and tapioca ratio and pH of solvent on physical properties of gel and edible plastics. Randomized Factorial Block Design were used. The two factors  were  porpotion of whey protein-starch mixture (0%, 20%, 40%, 60%, 80%, 100%) and pH of solvent ( 4, 7 and 9). Increasing of whey porpotion could increase solubility of gel but decrease gel’s lightness and texture. Increasing of pH could increase gel’s solubility and decrease lightness and texture. There was significant effect (p≤0,05) of whey porpotion and pH interaction on gel’s characters. Increasing of whey porpotion could increase tensile strength and decrease elongation and solubility of edible plastics but the increasing of tensile strength was not significant (p≥0,05). Increasing of pH could increase elongation and decrease tensile strength and plastic’s solubility. There wasn’t significant effect (p≥0,05) of whey porpotion and pH interaction on edible plastic’s characters. The result showed that whey addition had decreased plastic’s characters even at 100% whey ratio tensile strength and elongation value were zero, edible plastic could not be produced from 100% whey. Keywords: texture, solubility, elongation, tensile strength, interaction